1997
DOI: 10.1128/iai.65.12.5330-5333.1997
|View full text |Cite
|
Sign up to set email alerts
|

The role of Legionella pneumophila-infected Hartmannella vermiformis as an infectious particle in a murine model of Legionnaire's disease

Abstract: Legionella pneumophila is a bacterial parasite of many species of freshwater protozoa and occasionally an intracellular pathogen of humans. While protozoa are known to play a key role in the persistence of L. pneumophila in the environment, there has been limited research addressing the potential role of L. pneumophilainfected protozoa in the pathogenesis of human infection. In this report, the potential role of an L. pneumophila-infected amoeba as an infectious particle in replicative L. pneumophila lung infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 26 publications
0
46
0
1
Order By: Relevance
“…Fourthly, infection of amoebae by legionellae may contribute to its virulence against human cells. This is supported by the finding that L. pneumophila grown within amoebae are severalfold more invasive for macrophages and for intrapulmonary replication in mice (Brieland et al, 1997) compared with bacteria From protozoa to mammalian cells 253 grown on agar plates . Furthermore, after replication within amoebae, L. pneumophila becomes 1000-fold more resistant to antimicrobial compounds (Barker and Brown, 1995).…”
Section: Legionellae: Ecology and Transmissionmentioning
confidence: 81%
See 1 more Smart Citation
“…Fourthly, infection of amoebae by legionellae may contribute to its virulence against human cells. This is supported by the finding that L. pneumophila grown within amoebae are severalfold more invasive for macrophages and for intrapulmonary replication in mice (Brieland et al, 1997) compared with bacteria From protozoa to mammalian cells 253 grown on agar plates . Furthermore, after replication within amoebae, L. pneumophila becomes 1000-fold more resistant to antimicrobial compounds (Barker and Brown, 1995).…”
Section: Legionellae: Ecology and Transmissionmentioning
confidence: 81%
“…Secondly, Acanthamoeba species are capable of excreting L. pneumophila-filled vesicles, which may act as infectious particles upon inhalation (Berk et al, 1998). Thirdly, amoebae themselves harbouring large quantities of L. pneumophila may be inhaled and cause disease (Brieland et al, 1997). Figure 2 depicts the environmental interaction between legionellae and protozoa and its transmission to humans.…”
Section: Legionellae: Ecology and Transmissionmentioning
confidence: 99%
“…Results are the mean and standard deviation of three independent experiments. (Brieland et al, 1997;reviewed by Harb et al, 2000). Infected protozoa harbour many hundreds of organisms and could release them inside alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…By using various model systems it was shown that the interaction of Legionella and protozoa contributes to the infection process itself. After intracellular replication within protozoa L. pneumophila exhibits a higher stress resistance [3,29]. Mice inoculated with Legionella and Hartmannella develop more severe symptoms than those infected with either the bacterium or the amoeba alone [29].…”
Section: Legionella^protozoa Interactionsmentioning
confidence: 99%
“…After intracellular replication within protozoa L. pneumophila exhibits a higher stress resistance [3,29]. Mice inoculated with Legionella and Hartmannella develop more severe symptoms than those infected with either the bacterium or the amoeba alone [29]. However, the underlying mechanisms of this phenomenon are not yet understood.…”
Section: Legionella^protozoa Interactionsmentioning
confidence: 99%